Evaluation of Co-Processed Excipients for Fast Disintegration of Aspirin Tablets Prepared by Direct Compression (Nigerian Journal of Pharmaceutical Research, 2023)
Background: Co-processed excipients are popular for direct tablet compression gives added economic value to product formulation. Specific benefits of co-processed excipients include improved flow, compressibility, disintegrating effect, and masking undesirable properties of individual excipients.Objective: The aim of this study is to co-process physically modified (pregelatinized) Musa sapientum starch with lactose by fusion and evaluate the effect of the co-processed excipients on the disintegration properties of Aspirin tablet.Methods: Co-processed excipients were prepared from pregelatinized Musa sapientium starch and lactose by fusion in ratios of 1:1, 1:2 and 2:1 (BL1, BL2, and BL3 respectively) and evaluated for particle size, pH, moisture content, flow and swelling properties. Aspirin tablets were formulated using the excipients at ratio 5% W/W by direct compression. (FM1, FM2, FM3 respectively). Sodium starch glycolate (FSG) tablet was also prepared as the standard and the formulations were assessed for hardness, friability and disintegration time. Data were analyzed using ANOVA.Results: The co-processed excipients possessed excellent flow having a Carr’s index between 18.39-20.78 and Hausner’s ratio ≤ 1.25.BL1 had the highest swelling profile while BL3 had the lowest. Formulation FM1 and FM2 had the highest tensile strength of (0.16 N/cm2). Disintegration time of FM3 (4.28 min) was comparable to that of FSG (4.15 min).Conclusion: Co-processing pregelatinized Musa sapientium starch and lactose by fusion influenced tablet disintegration and has potential to be used in manufacture of fast dissolving tablet formulations